Pharmacokinetics and bioavailability of a new long-acting insulin analog in healthy Chinese volunteers: an open, randomized, single-dose, two-period and two-sequence cross-over study - Ke-Guang Chen; Ye-Hui Zhang; Pan-Pan Ye; Xue-Hu Gao; Lin-Lin Song; Hai-Yan Zhou; Qian Li; Fu-Rong Zhao; Jin-Yi Shi; Xin-Mei Yang; Kai Shen; Sheng Feng; et al. (Frontiers Media S.A., 2023)
Objectives: INS068 is a novel, soluble, and long-acting insulin analog. In this study, we evaluated the pharmacokinetics and relative bioavailability of two formulations of INS068 in healthy Chinese subjects: a reference formulation packaged in vials and administered via syringe (R), and a test formulation packaged and administered via pen injector (T).Methods: A randomized, open-label, two-period, two-sequence crossover study was conducted with 24 healthy Chinese subjects. Subjects were randomized and administered subcutaneously in the abdomen at 0.4 U/kg of test or reference INS068 injection according to an open crossover design. INS068 concentrations in the serum were measured using LC-MS/MS, and the pharmacokinetic parameters of maximum concentration (Cmax) and area under the concentration-time curve (AUC0-t and AUC0-∞) were used to evaluate relative bioavailability.Results: After a single dose at 0.4 U/kg, the median Tmax of INS068 was 12 h for both formulations, and the mean t1/2 for T and R was 13.0 h and 12.6 h, respectively. The geometric means of Cmax and AUC0-∞ were 3.99 nmol/L and 120 h·nmol/L for the T, and 4.05 nmol/L and 117 h·nmol/L for the R, respectively. The geometric mean ratios of Cmax, AUC0-t and AUC0-∞ of T over R were 98.7% (90% CI: 92.7%-105.2%), 102.6% (90% CI: 100.0%-105.3%) and 102.8% (90% CI: 100.1%-105.5%).Conclusion: The overall PK profile of the two formulations of INS068 injection was comparable in healthy subjects, and the pen injector of INS068 had adequate safety and tolerability, supporting it as a new formulation in a phase III study and bridging PK data from early phase clinical trials.Clinical Trial Registration:clinicaltrials.gov, identifier: NCT05336071